Health‐related quality of life impacts upon 5‐year survival after coronary artery bypass surgery. Issue 12 (24th November 2022) - Bishawi, Muath; Hattler, Brack; Almassi, G. Hossein; Quin, Jacquelyn A.; Grover, Frederick L.; Collins, Joseph F.; Ebrahimi, Ramin; Wolbrom, Daniel H.; Shroyer, A. Laurie; ,
Abstract: Background: Poor preoperative health‐related quality of life (HRQoL) has been associated with reduced short‐term survival after coronary artery bypass graft (CABG) surgery; however, its impact on long‐term mortality is unknown. This study's objective was to determine if baseline HRQoL status predicts 5‐year post‐CABG mortality. Methods: This prespecified, randomized on/off bypass follow‐up study (ROOBY‐FS) subanalysis compared baseline patient characteristics and HRQoL scores, obtained from the Seattle Angina Questionnaire (SAQ) and Veterans RAND Short Form‐36 (VR‐36), between 5‐year post‐CABG survivors and nonsurvivors. Standardized subscores were calculated for each questionnaire. Multivariable logistic regression assessed whether HRQoL survey subcomponents independently predicted 5‐year mortality ( p  ≤ .05). Results: Of the 2203 ROOBY‐FS enrollees, 2104 (95.5%) completed baseline surveys. Significant differences between 5‐year post‐CABG deaths ( n  = 286) and survivors ( n  = 1818) included age, history of chronic obstructive pulmonary disease, stroke, peripheral vascular disease, renal dysfunction, diabetes, lower left ventricular ejection fraction, atrial fibrillation, depression, non‐White race/ethnicity, lower education status, and off‐pump CABG. Adjusting for these factors, baseline VR‐36 physical component summary score ( p  = .01), VR‐36 mental component summary score ( p  < .001), and SAQ physical limitation score ( p  = .003) were all associated with 5‐year all‐cause mortality. Conclusions: Pre‐CABG HRQoL scores may provide clinically relevant prognostic information beyond traditional risk models and prove useful for patient‐provider shared decision‐making and enhancing pre‐CABG informed consent.